Analisis Pengelolaan Sumber Daya Manusia dalam Upaya Meningkatkan Kualitas Pelayanan Pasien IGD pada RSUD Oto Iskandar Di Nata - Silvi Fitri Utami; Harry Nugraha (Universitas Nusantara PGRI Kediri, 2024)
This study aims to analyze human resource management in an effort to improve the quality of emergency room patient services at Otista Regional Hospital. Problem data was obtained based on the Otista Regional Hospital Strategic Plan for 2021-2026. The research used qualitative research methods which describe based on data obtained through interview techniques and distributing questionnaires to the research location at Otista Hospital, Bandung Regency. The techniques used to analyze data are data reduction, data presentation, and drawing conclusions. The research results showed that based on questionnaire calculations, the average result was 4.65 with a very high index. Meanwhile, for the results of the questionnaire related to IGD HR, the average result was 4.28 with a very high index. The efforts made by Otista Regional Hospital to maintain this condition include ongoing training and guidance for human resources so that HR management at Otista Regional Hospital can continue to provide quality services to patients, especially emergency room patients.